The Effect of a Phytobiotic, Probiotic, and Their Combination as Feed Additives on Growth Performance of Weaned Holstein Male Dairy Calves - Ting Liu; David P. Casper; Jiang Hu (Animals)
A phytobiotic extract (PE; proprietary blend of garlic, anise, cassia, rosemary, and thyme) has been shown to enhance dry matter intake (DMI) and gut health, while ExCell (EX), a probiotic (Lactobacillus acidophilus fermentation product), has been shown to improve gut health and growth performance of growing Holstein calves. The hypothesis was the combination could be synergistic for enhancing post-weaning calf growth performance. Seventy-seven Holstein male calves (73.6 BW ± 7.5 kg SD) at 49 d of age were blocked by body weight (BW) and randomly assigned to four treatments using a randomized complete block design with a 3 wk experimental period. Treatments were: (1) Control (CN): calf starter (CS) without PE or EX; (2) PE: CS with 275.6 g/ton Apex to supply 0.6 g/d; (3) EX: CS with 0.22% EX to supply 5 g/d; and (4) PEEX: CS with PE and EX added at the same rates. Individual calf BW was weighed weekly and they were fed ad libitum a 22% CP CS with amounts fed and orts recorded daily. Body weight was greater (p < 0.05) for calves fed EX (81.3, 80.8, 84.8, and 84.2 kg for CN, PE, EX, and PEEX, respectively) compared with calves fed CN and PE with calves fed PEEX being intermediate and similar (p > 0.10). Average daily gains (ADGs) showed a trend (p < 0.10) for calves fed EX (965.5, 984.3, 1052.8, and 989.1 g/d) compared with calves fed the remaining treatments. Dry matter intake (DMI; 2.19, 2.18, 2.31, and 2.14 kg/d) and feed conversions (0.45, 0.46, 0.45, and 0.45 kg BW gain/kg DMI) were similar (p > 0.10) among calves fed all treatments. Blood urea nitrogen concentrations (14.7, 14.6, 14.9, and 13.4 mg/dL) were similar (p > 0.10) among calves fed all treatments. Feeding a probiotic improved BW gains of post-weaning Holstein male calves, but the PE alone or in combination with EX (i.e., PEEX) was not beneficial for enhancing post-weaning growth performance. These results demonstrated that feeding specific additives alone or in combination was not beneficial to calf growth performance.